Spillovers from the Maturing of China's Economy - Dizioli, Allan (IMF Working Papers; Working Paper ;, 2016)
China's transition to a new growth model continues and the impact has been felt across the globe. Several trends contribute to the 'maturing' of China's economy: i) structural slowing on the convergence path; ii) on-shoring deepening; and iii) demand rebalancing from investment towards consumption. In the short term, financial stress may lead to a cyclical slowdown. This paper discusses and quantifies spillovers to the global economy from these different developments. The analysis is undertaken using the APDMOD and G20MOD, both modules of the IMF's Flexible System of Global Models. For plausible values of these developments, the overall impact on the global economy is not large. However, the impact on China's closest trading partners and commodity exporters can be notable.